Do incarcerated male juvenile recidivists differ from first-time offenders on self-reported psychopathic traits? A retrospective study - Pechorro, Pedro Fernandes Santos (2019)
The current study analyzed the relation between recidivism and self-reported psychopathic traits, more specifically the callous-unemotional, impulsivity, and narcissism dimensions of the psychopathy construct. The Antisocial Process Screening Device – Self-Report (APSD-SR) and other self- report instruments independently measuring the three different dimensions of psychopathy (that is, Inventory of Callous-Unemotional Traits, Barratt Impulsiveness Scale-11, Narcissistic Personality-13) were completed by a sample of incarcerated male juvenile offenders (N = 244) who were retrospectively classified as recidivists versus non-recidivists. The only statistically significant relation found between recidivism and self-reported psychopathic traits after controlling for age and socioeconomic status was with the impulsivity dimension of the APSD-SR. Additionally, results showed that recidivism was associated with alcohol use but not with drug use or crime seriousness.